Accuracy of 3 new methods for intraocular lens power selection. Issue 3 (March 2017) - Kane, Jack X.; Van Heerden, Anton; Atik, Alp; Petsoglou, Constantinos
Abstract : Purpose : To evaluate the accuracy of 3 new methods for intraocular lens (IOL) power selection (Hill‐Radial Basis Function [Hill‐RBF] method, FullMonte method, and the Ladas Super Formula) compared with that of the Holladay 1 and Barrett Universal II formulas. Setting : Ophthalmology Department, Alfred Hospital, Melbourne, Australia. Design : Retrospective case series. Methods : Patients who had uneventful cataract surgery with insertion of the Acrysof IQ SN60WF IOL over 5 years were included in the study. Data obtained from the electronic medical record and the IOLMaster device were entered into the respective calculators using self‐designed computer programs. Using optimized lens constants, the predicted refractive outcome using each of the 5 methods/formulas was calculated and compared with the actual refractive outcome to give the prediction error. Eyes were separated into subgroups based on axial length as follows: short (≤22.0 mm), medium (>22.0 to <24.5 mm), medium‐long (≥24.5 to <26.0 mm), and long (≥26.0 mm). Results : The study comprised 3122 eyes of 3122 patients. A statistically significant difference in the mean absolute prediction error (MAE) between the 5 methods for IOL power calculation was found ( P < .001), with the Barrett Universal II formula being the most accurate. The Ladas Super Formula had the third lowest MAE, the Hill‐RBF the fourth lowest MAE, and the FullMonte the highest MAE of the 5 methods assessed. Conclusion : New methods for predicting the postoperative refraction failed to yield more accurate results than current formulas.